Measures of poverty and inequality in the countries and regions of EU - Society for the Study of Economic Inequality, Palma de Mallorca; Longford, Nicholas T.; Pittau, Maria Grazia; Zelli, Roberto; Massari, Riccardo (Palma de Mallorca, 2010)
"The European Union Survey on Income and Living Conditions (EU-SILC) is the main source of information about living standards and poverty in the member states of the European Union. It provides reliable statistics at national level but sample sizes do not allow reliable estimates at sub-national level, despite a rising demand from policy makers and local authorities. We provide a comprehensive map of median income, inequality (Gini coefficient and Lorenz curve) and poverty (poverty rates), at country and regional levels, based on the equivalized household income in all the countries in which EU-SILC is conducted. We focus on personal income distribution within regions as opposed to per capita income distribution across regions to give a deeper insight into regional disparities. Small-area estimation is applied to improve estimates in regions with small sample size. Uncertainty of such complex non-linear statistics is assessed by bootstrap methods. Household-level sampling weights are taken into account in both the estimates and their relative bootstrapped standard errors."